An Overview of Court Mediation in the State Courts of Singapore - LOW, Joyce (Institutional Knowledge at Singapore Management University, 2015)
This is a chapter from George Lim and Danny McFadden (ed), Mediation in Singapore: A Guide (Sweet & Maxwell, Singapore, 2015). The chapter traces the development of court mediation in Singapore, the key features of court mediation and the practical implications of the principles underlying the model for lawyers and their clients.